2017
DOI: 10.1016/j.yhbeh.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Blunted cortisol response to acute pre-learning stress prevents misinformation effect in a forced confabulation paradigm

Abstract: Research examining the effects of stress on false memory formation has been equivocal, partly because of the complex nature of stress-memory interactions. A major factor influencing stress effects on learning is the timing of stress relative to encoding. Previous work has shown that brief stressors administered immediately before learning enhance long-term memory. Thus, we predicted that brief stress immediately before learning would decrease participants’ susceptibility to subsequent misinformation and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
1
1
0
4
Order By: Relevance
“…Further, by enhancing memory for the video, pre-encoding stress could help improve subsequent source monitoring and reduce susceptibility to misinformation from the synopsis. Consistent with this idea, in studies with young adults, researchers have found that stress prior to a witnessed event both improved memory accuracy (Hoscheidt, LaBar, Ryan, Jacobs, & Nadel, 2014) and reduced susceptibility to post-event misinformation (Hoscheidt et al, 2014;Zoladz et al, 2017). However, no such effects were found in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…Further, by enhancing memory for the video, pre-encoding stress could help improve subsequent source monitoring and reduce susceptibility to misinformation from the synopsis. Consistent with this idea, in studies with young adults, researchers have found that stress prior to a witnessed event both improved memory accuracy (Hoscheidt, LaBar, Ryan, Jacobs, & Nadel, 2014) and reduced susceptibility to post-event misinformation (Hoscheidt et al, 2014;Zoladz et al, 2017). However, no such effects were found in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…En la confabulación pueden presentarse afirmaciones y acciones inintencionalmente incongruentes con el pasado, el presente y el futuro del paciente, y aunque es una alteración poco frecuente de la memoria y generalmente se encuentra en pacientes con afectación de PsicoesPacios / Vol. 15 n. 26 / enero-Junio, 2021 / issn-e: 2145-2776 esta, también puede encontrarse en sujetos con memoria y habilidades de aprendizaje normales (Dalla Barba et al, 2020;García Barco, 2020;Martín Juan et al, 2018;Zoladz et al, 2017).…”
Section: Desarrollo Y Discusiónunclassified
“…La formación y evocación de recuerdos ha sido una pauta fundamental en el estudio de la neurociencia moderna, al igual que el hipocampo como región crítica para la formación de recuerdos episódicos (Molina, 2016;Terranova et al, 2019;Voss et al, 2019;Zoladz et al, 2017). El daño en esta estructura puede provocar la incapacidad de formar nuevos recuerdos, sin perjuicio de las memorias previamente adquiridas.…”
Section: Etiologíaunclassified
See 2 more Smart Citations